THE MAPPING DISTRIBUTION Of SEA SURFACE TEMPERATURE AND RELATION WITH THE CATCH OF CAKALANG (Katsuwonus Pelamis) USING THE MODIS AQUA SATELLITE IMAGE IN THE WATERS OF WEST SUMATERA - Harahap, Mutiara Alkayakni; ', Irwandi; ', Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in May by 2015 at Pelabuhan Perikanan Samudera Bungus, West Sumatra. The purpose of this study is to create a map of the fishing ground Cakalang (Katsuwonus pelamis) in West Sumatera by using Aqua MODIS satellite image. This study used a survey and spasial analysis . The survey methods used to obtain data on secondary i,e the catch is Cakalang (Katsuwonus pelamis) from January-December 2013. The fishing ground of the Cakalang used in this study are at 00 ' N – 40 50 26 ' S and 980 08 ' E – 1000 57 ' E.The distributionof sea surface temperature analyzed satellite imagery Seadas 7.2 rangging from 28,98-31,19 0C whereas maximal catches as much as 14.4500 Kg in the East season.Keywords:sea surface temperature, satellite image, MODIS Aqua, (Katsuwonus pelamis)